Conceptualization Of Regulations On The Use Artificial Intelligence Technology In Indonesia - Siti - Mariyam (Faculty of Law, Universitas Pekalongan, 2024)
Artificial Intelligence (AI) has become an integral part of everyday life, and this technology has now transformed the way we work and has controlled various industries and sectors of human life. The potential benefits of AI today are enormous, including increased efficiency, productivity, and innovation. However, the use of AI also raises concerns about ethical, legal, social, and privacy issues for society. This paper aims to measure the benefits of AI in human life, the urgency of regulating the use of AI technology, and the concept of regulating the use of AI in Indonesia. This paper reviews various literature and studies related to AI and its impact on society. The results show that AI has the potential to bring significant benefits to human life, but its unregulated use can also pose significant risks. Therefore, it is important to establish regulations that address AI concerns from ethical, legal, and social perspectives. This paper also proposes a concept of regulating AI in Indonesia that includes general requirements, development to use and sanctions, and AI use must also uphold ethical and legal principles, such as transparency, accountability, and human rights protection. This paper emphasizes the importance of balancing the benefits and risks of AI to ensure safe and responsible use in society.